Peningkatan Kualitas Laporan Keuangan UMKM di Tangerang Berbasis Teknologi Informasi - Imelda, I; Meidiyustiani, Rinny; Lestari, Indah Rahayu (Indonesian Journal of Emerging Trends in Community Empowerment, 2024)
The presence of an accounting information system (SIA) is one of the means fo Micros, Small, an Medium Enterprises (MSMEs) for preparing financial report that can ber provide financial reports quickly and accurately. MSMEs of food packaging cluster in Karang Tengah, Tangerang still run their businesses traditionally, then they realize the importance of finacial statement to advance their businisses. Constraints encountered by MSMEs are: (1) Lack of knowledge regarding financial statements, (2) Do not know types of financial statements, (3) Do not understand te importance of financial statements for businesses, (4) difficulties in obtaining funding from banks, (5) Has ever made financial statements using computer. The solutions are: (1) providing basic knowledge abaout financial statements, (2) introducing types of financial statements based on Financial Accounting Standards for Micro, Small, and Medium Enterprises (FAS MSMEs), (3) Explaining the importance of financial statements for business progress, (4) Providing training and skill in preparing financial reports based using FAS MSMEs, (5) Using accounting information system application to facilitaate MSMEs for preparing financial statements. The method are: preparation, implementation which is an evaluation of activities. The activity material included the introduction of basic concepts of financial statements, introduction of financial satements benefit, to the preparation of financial statements based on FAS MSMEs using lamikro application which made by Cooperatives and Small Micro Enterprises Ministry (CSMEs Ministry). After the training, increased understanding and improvement of MSMEs skill for preparing financial statements, especially using Lamikro application, to supporting their businesses. coaching periodically until MSMEs can preparing financial statements independently.